Sieges and ceasefires in Syria's civil war: Lessons learned as regional players undermine new approach by UN mediator - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2015)
Representatives of the Group of Friends of the Syrian People, an international alliance that nominally supports the Syrian opposition, met in Berlin in March 2015 on the fourth anniversary of the Syrian revolt. Participants in the meeting discussed ways to revive the mission of UN mediator Staffan de Mistura, whose efforts for achieving a ceasefire in Aleppo - Syria's former commercial and industrial hub - have gone nowhere. Germany has been particularly supportive of de Mistura. But the main players in Syria and their regional supporters have shown little willingness to curb the violence, as the conflict, together with Yemen, is at the heart of what is increasingly perceived as a Sunni-Shia schism. Germany is committed to finding a political solution in Syria that addresses the regional dimension of the conflict. But this is unlikely to happen without a thaw between Iran and Saudi Arabia that would allow for tackling sticky political issues behind the religious rhetoric. (SWP Comments)
Keywords: 320